Tripodal, Squaramide-Based Ion Pair Receptor for Effective Extraction of Sulfate Salt - Damian Jagleniec; Marcin Wilczek; Jan Romański (Molecules, 2021)
Combining three features—the high affinity of squaramides toward anions, cooperation in ion pair binding and preorganization of the binding domains in the tripodal platform—led to the effective receptor 2. The lack of at least one of these key elements in the structures of reference receptors 3 and 4 caused a lower affinity towards ion pairs. Receptor 2 was found to form an intramolecular network in wet chloroform, which changed into inorganic–organic associates after contact with ions and allowed salts to be extracted from an aqueous to an organic phase. The disparity in the binding mode of 2 with sulfates and with other monovalent anions led to the selective extraction of extremely hydrated sulfate anions in the presence of more lipophilic salts, thus overcoming the Hofmeister series.